2012
DOI: 10.1155/2012/571946
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Therapy for Locally Recurrent Breast Cancer

Abstract: Approximately one-third of all breast cancer patients experience local recurrence of their tumor after initial treatment. As initial treatment often employs the use of radiation therapy (RT), the standard of care for local breast cancer recurrence after initial breast conserving therapy has traditionally been surgical intervention with mastectomy. However, recent attempts to preserve the intact breast after recurrence with local excision have revealed a potential need for RT in addition to repeat breast conser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…Notably, the majority of patient achieved very good local control after treatment of ILRR, with comparable rates of second-ILRR; 8.2% of the salvage mastectomy population and 12.5% in the repeat breast conserving surgery group. In-breast recurrences after repeat breast-conserving surgery ranges between 7% to 38% (36 to 120 month follow-up) 11, 18 . Gentilini et al found a higher second local failure rate than in our trial; 27% of 161 IBTR cases treated by repeat breast conservation 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the majority of patient achieved very good local control after treatment of ILRR, with comparable rates of second-ILRR; 8.2% of the salvage mastectomy population and 12.5% in the repeat breast conserving surgery group. In-breast recurrences after repeat breast-conserving surgery ranges between 7% to 38% (36 to 120 month follow-up) 11, 18 . Gentilini et al found a higher second local failure rate than in our trial; 27% of 161 IBTR cases treated by repeat breast conservation 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Sexual well-being showed best results in the group of mastectomy ( Table 2). Despite these trends, there were no clinically important differences of questionnaire scores within (15) 53.8% (14) 42.3% (11) 3.6% (1) 51.4% (18) 34.3% (12) 14.3% (5) 44.2% (23) 38.5% (20) 17.3% (9) the groups. Higher satisfaction scores in most items were related to higher age (> 75 years) in every group, but even taking this into consideration there was still no evidence of significant differences.…”
Section: Resultsmentioning
confidence: 79%
“…Patients with IBTR without evidence of distant metastasis are treated with curative intent, aiming for local disease control through wide local excision or mastectomy, combined with selective use of (re)irradiation depending on previous treatments. Although lymph node staging is an integral component of primary breast cancer treatment, the optimal management of the lymph nodes in patients with IBTR has not been standardized.…”
Section: Introductionmentioning
confidence: 99%